Above-ground and Below-ground Biomass situation of Milke-Jaljale Rangeland at Different Altitudinal Gradient - Limbu, D.K.; Koirala, M. (Our Nature, 2012)
Rangeland conservation has been increasingly interested for carbon reduction and mitigation of climate change, because of carbon storage. Thus, biomass of the rangeland remains pivotal regarding carbon sequestration on rangeland. Present study was conducted in high altitude rangeland at Jaljale (4000 m), Gorujure (3500 m) and Milke (3000 m) on September, 2010 with an objective to estimate rangeland biomass following the total harvesting method. Result revealed that biomass of high altitude rangeland has relatively high value (1.50 t/ha for both above ground biomass and 43.48 t/ha for below ground biomass) compared to low altitude rangeland (0.35 t/ha for above ground biomass and 16.93 t/ha for below ground biomass). Similarly, monocot plant density play crucial role for biomass contribution of rangeland. DOI: http://dx.doi.org/10.3126/on.v9i1.5740